Answer:
x=14
Explanation:
Step-1 :
Multiply the coefficient of the first term by the constant 1 • 28 = 28
Step-2 :Find two factors of 28 whose sum equals the coefficient of the middle term, which is -16 .
-28 + -1 = -29
-14 + -2 = -16
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -14 and -2
x2 - 14x - 2x - 28
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-14)
Add up the last 2 terms, pulling out common factors :
2 • (x-14)
Step-5 : Add up the four terms of step 4 :
(x-2) • (x-14)
Answer:
x=14